2003
DOI: 10.1161/01.cir.0000091409.53101.e8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Serotonin Transporter Gene and Pulmonary Hypertension in Chronic Obstructive Pulmonary Disease

Abstract: Background-The serotonin transporter (5-HTT) is involved in the pulmonary artery smooth muscle hyperplasia that leads to pulmonary hypertension (PH). Because hypoxia and 5-HTT gene polymorphism control 5-HTT expression, we examined 5-HTT gene polymorphism and PH in hypoxemic patients with advanced chronic obstructive pulmonary disease (COPD). Methods and Results-In 103 patients with COPD recruited in France (nϭ67) and the UK (nϭ36), we determined 5-HTT gene polymorphism and pulmonary artery pressure (PAP) meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
110
1
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(129 citation statements)
references
References 18 publications
11
110
1
7
Order By: Relevance
“…Individuals with spontaneous primary pulmonary hypertension more frequently have the 5HTTLPR LL genotype. Unlike primarily hypertensive patients, hypoxic patients with COPD do not differ from controls in 5HT-TLPR genotype frequencies; however, the LL variant of 5 HTTLPR in COPD patients, who have higher SERT expression in pulmonary artery cells, was associated with significantly more severe pulmonary hypertension compared to LS or SS patients (Eddahibi et al 2003), what is in accordance with findings in rodent models (Eddahibi et al 2000).…”
Section: Serotonin Transportersupporting
confidence: 82%
“…Individuals with spontaneous primary pulmonary hypertension more frequently have the 5HTTLPR LL genotype. Unlike primarily hypertensive patients, hypoxic patients with COPD do not differ from controls in 5HT-TLPR genotype frequencies; however, the LL variant of 5 HTTLPR in COPD patients, who have higher SERT expression in pulmonary artery cells, was associated with significantly more severe pulmonary hypertension compared to LS or SS patients (Eddahibi et al 2003), what is in accordance with findings in rodent models (Eddahibi et al 2000).…”
Section: Serotonin Transportersupporting
confidence: 82%
“…N Group 3, PH due to lung diseases and/or hypoxia: one study has shown that serotonin gene polymorphism appears to determine the severity of PH in hypoxaemic patients with chronic obstructive pulmonary disease (COPD) [34]. Based on published series, the incidence of significant PH in COPD patients with at least one previous hospitalisation for exacerbation of respiratory failure is 20%.…”
Section: Genetics Epidemiology and Risk Factors Of Pulmonary Hypertementioning
confidence: 99%
“…Recommendations for a PH referral centre are summarised in table 34. ESC/ERS GUIDELINES N. GALIÈ ET AL.…”
Section: Definition Of a Pulmonary Arterial Hypertension Referral Centrementioning
confidence: 99%
“…In one report, the L allele was found to be more prevalent in patients with IPAH than in control subjects (7,15). In a study of patients with chronic obstructive pulmonary disease, 56% of patients had the LL genotype, which was associated with increased SERT transcription and more severe pulmonary hypertension (PH) (16). The role of SERT polymorphisms in the penetrance and severity of PAH is unknown.…”
mentioning
confidence: 99%